Penerapan Metode Field Trip Berbantuan Flipbook untuk Meningkatkan Keterampilan Menulis Teks Deskripsi Pada Siswa Sekolah Menengah Pertama : Implementation of the Flipbook-Assisted Field Trip Method to Improve Descriptive Text Writing Skills in Junior High School Students - Ni Kadek Juli Purnama Wati; I Nyoman Yasa; I Putu Mas Dewantara (Jurnal IKA, 2026)
This study aims to describe the implementation, learning outcomes, and students’ responses to the application of the flipbook-assisted field trip method in teaching descriptive text writing to junior high school students. This study employed Classroom Action Research (CAR), which involved the stages of initial reflection, planning, implementation, observation, and reflection. The subjects of this study were an Indonesian language teacher and 36 students of Class VII-5. The data were collected using observation, tests, and questionnaires. The data in this study were analyzed using qualitative descriptive and quantitative descriptive data analysis techniques. The results of this study indicate an improvement in students’ descriptive text writing skills. The implementation in Cycle I was not carried out effectively; however, in Cycle II, it was implemented effectively after revisions were made based on the results of the reflection in Cycle I. The students’ average score at the pre-implementation stage was only 61.20. It then increased to 69.6 in Cycle I, which was categorized as Fair, and further improved to 80.2 in Cycle II, which was categorized as Good. Thus, there was an increase of 10.6% in the average score from Cycle I to Cycle II. In addition, in Cycle II, all 36 students achieved scores above the minimum mastery criterion, resulting in 100% classical mastery, which indicates that the instructional intervention was successful. In addition, the average score of students’ responses to the implementation of the flipbook-assisted field trip method also increased, from 40.14 in Cycle I, categorized as positive, to 45 in Cycle II, categorized as very positive. Based on these findings, it can be concluded that the implementation of the flipbook-assisted field trip method is effective in improving students’ descriptive text writing skills and in obtaining very positive responses from students.